Telerehabilitation during the COVID-19 pandemic, what are the determinants of satisfaction for chronic diseases? a retrospective study - Roy, Anne laure; Duruflé, Aurélie; Piette, Patrice; Fraudet, Bastien; Lofficial, Vincent; Gallien, Philippe (Frontiers in Rehabilitation Sciences, 2023)
Background During the Covid-19 health crisis, telerehabilitation provided a solution to ensure the continuity of care. Since then, it has been offered as an alternative to face-to-face rehabilitation in chronic conditions. Data measuring satisfaction are essential to adapt and increase the effectiveness of this type of programme. Aim and scope This research focused on determining the most significant determinants of participant satisfaction in a telerehabilitation programme. Methods We conducted a retrospective study by analysing the satisfaction questionnaire used from the start of the programme. Result Two hundred and ten (210) participants completed the programme; 180 questionnaires were filled in and 175 analyzed of which 70 with chronic low back pain (CLBP), 59 for multiple sclerosis (MS) and 22 with parkinson's disease (PD). Satisfaction was high for all participants (scoring out of 10, mean = 8.22 sd = 1.53), but the determinants reported for the three main conditions involved in the programme differed. Main determinant was “benefice” for CLBP (p = 1.23e-05), “home exercises adapted” for MS (p = 0.000679) and “interest in staying at home” for PD (p = 1.84e-05). Conclusion Depending on the context of the condition/disease, the drivers of satisfaction were not identical. Knowledge of these determinants will allow us to further improve the programme. However, some unresolved questions remain regarding the place of therapists, their role and the skills required for a successful telerehabilitation programme. Further studies are required to understand the impact.